2011
DOI: 10.1021/la202377t
|View full text |Cite
|
Sign up to set email alerts
|

Structure of ABCA Tetrablock Copolymer Vesicles and Their Formation in Selective Solvents: A Monte Carlo Study

Abstract: Vesicles formed by ABCA tetrablock copolymers in solvents that are selective for block A are studied using the Monte Carlo simulation. Simulation results show that the chain length ratio and hydrophobicity of blocks B and C are key factors determining the hydrophobic layer structure of the vesicles. If the B and C blocks are of the same hydrophobicity, the longer block C tends to form the closed hydrophobic layer, whereas the shorter block B is located on the outer surface of the closed hydrophobic layer. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
(42 reference statements)
2
27
0
Order By: Relevance
“…The phenomenon shown in Fig. However, due to the block length effect, the outer solvophobic layer of the A 2 B 7 C 5 A 2 asymmetric vesicle is always occupied by the shorter blocks C. This is consistent with the simulation results for ABCA asymmetric vesicle reported by Cui et al 32 . Therefore, it can be concluded that longer block length can compensate the lower solvophobic interaction of block B to a certain degree in A 2 B 7 C 5 A 2 tetrablock copolymer system.…”
Section: A 2 B 8 C 4 a 2 Tetrablock Copolymerssupporting
confidence: 91%
See 1 more Smart Citation
“…The phenomenon shown in Fig. However, due to the block length effect, the outer solvophobic layer of the A 2 B 7 C 5 A 2 asymmetric vesicle is always occupied by the shorter blocks C. This is consistent with the simulation results for ABCA asymmetric vesicle reported by Cui et al 32 . Therefore, it can be concluded that longer block length can compensate the lower solvophobic interaction of block B to a certain degree in A 2 B 7 C 5 A 2 tetrablock copolymer system.…”
Section: A 2 B 8 C 4 a 2 Tetrablock Copolymerssupporting
confidence: 91%
“…However, in the case of 1 r = in region 3, due to the same solvophobic interactions of blocks B and C, the probability for either blocks B or C locating on the outer solvophobic layer is equal32 . These vesicles possess different inner and outer solvophobic layers and their solvophobic layers are multicompartment.…”
mentioning
confidence: 99%
“…In addition to extensive experimental investigations, theoretical studies and computer simulations provide powerful tools for studying the self-assembly of block copolymer solutions. [29][30][31][32][33][34][35] The majority of investigations have focused on the effect of the properties of the copolymer or selective solvent on aggregate morphologies, such as copolymer composition, volume fraction, configuration, and selectivity strength. Using simulated annealing, Sun et al studied the self-assembly of diblock copolymers in selective solvents (using only one type of solvent).…”
Section: Introductionmentioning
confidence: 99%
“…31 For an A-B-C-A tetrablock copolymer in selective solvents, the chain length ratio and hydrophobicity of blocks B and C were key factors in determining the hydrophobic layer structure of the vesicles. 32 In their study on asymmetric vesicles constructed from an AB/CB diblock copolymer mixture in a selective solvent for A and C blocks, they found that the vesicle structure sequence depends on the composition of the mixture, the chain length of the hydrophilic block, and the solution pH. 33 Liang's group investigated the microstructures assembled from amphiphilic triblock copolymers in selective 6 solvents using the DPD approach, and reported the different pathways involved in the formation of aggregates.…”
mentioning
confidence: 99%
“…Some of the self‐consistent field theories commonly applied to block copolymer melts have also been further adapted to explain micellar assemblies Together, these simulations provide an atom‐level understanding of the behavior that lead to the polymer vesicle formation . Over the last two decades, various simulation techniques, such as Monte‐Carlo, Brownian dynamics, molecular dynamics (MD) and dissipative particle dynamics (DPD), have been used to study both lipid and polymer membranes . Evidently, simulating polymer self‐assembly with atom resolution is limited by computing power.…”
Section: Computational Studiesmentioning
confidence: 99%